Atlas of the vascular flora of the Iberian Peninsula biodiversity hotspot (AFLIBER). Issue 10 (20th July 2021) - Ramos‐Gutiérrez, Ignacio; Lima, Herlander; Pajarón, Santiago; Romero‐Zarco, Carlos; Sáez, Llorenç; Pataro, Luciano; Molina‐Venegas, Rafael; Rodríguez, Miguel Á.; Moreno‐Saiz, Juan Carlos
Abstract: Motivation: We accessed published and unpublished floristic sources to compile a comprehensive species list of the Iberian–Balearic terrestrial vascular flora and generate AFLIBER, an accurate floristic database of georeferenced plant occurrence records. Main type of variable contained: Species distribution data totalling 1, 824, 549 plant occurrence records corresponding to 6, 456 species and subspecies. Spatial location and grain: The western Mediterranean, including inland territories of Spain, Portugal and Andorra and the adjacent archipelagos of Berlengas, Columbretes and the Balearic Islands, covered by 6, 316 UTM quadrangular grid cells of 10 km resolution. Time period: All distributional trustable records were considered to create the AFLIBER database, most of them dating from the 1960s onwards. Major taxa and level of measurement: Terrestrial vascular plant species and subspecies. Software format: Data are supplied as comma‐separated text (csv) files.